Critical Congenital Heart Disease Detection in the Screening Era: Do Not Neglect the Examination! - Deepika Sankaran; Heather Siefkes; Frank F. Ing; Satyan Lakshminrusimha; Francis R. Poulain (Thieme Medical Publishers, Inc., 2021)
Pulse oximetry oxygen saturation (SpO2)-based critical congenital heart disease (CCHD) screening is effective in detection of cyanotic heart lesions. We report a full-term male infant with normal perfusion who had passed the CCHD screening at approximately 24 hours after birth with preductal SpO2 of 99% and postductal SpO2 of 97%. Detection of a loud systolic cardiac murmur before discharge led to the diagnosis of pulmonary atresia (PA) with ventricular septal defect (PA-VSD) by echocardiogram. The infant was transferred to a tertiary care center after initiation of prostaglandin E1 (PGE1) therapy. Throughout the initial course, he was breathing comfortably without respiratory distress or desaturations on pulse oximetry. We believe that this is the first documented report of PA missed by CCHD screening. Thorough and serial clinical examinations of the newborn infant proved vital in the timely diagnosis of this critical disease. We review the hemodynamics and the recent literature evaluating utility of CCHD screening in the diagnosis of PA-VSD. Pulse oximetry-based CCHD screening should be considered a tool to enhance CCHD detection with an emphasis on detailed serial physical examinations in newborn infants.